An academic challenge to the entrepreneurial university: the spatial power of the 'Slow Swimming Club'. Issue 2 (1st February 2020) - Jones, David R.; Patton, Dean
ABSTRACT: The entrepreneurial university is a vague notion that has evolved by applying the concepts of enterprise and entrepreneurship to a university context. The blurring of enterprise with entrepreneurship has allowed the entrepreneurial university to be increasingly underpinned by a managerialist discourse, typified by functionalisation and marketisation; culminating in academic disempowerment, dissatisfaction and subsequent disengagement. In response to such dissatisfaction, this paper reflects on a playful space, called the Slow Swimming Club (SSC), produced by several academics. The research takes a collective auto-ethnographic approach and employs Foucault's heterotopology, as a conceptual frame, to understand the collective impact of this SSC entrepreneuring space. We relate the disconnection of the SSC to the process of critically connecting academics, back to their universities and consider whether such academic resistance, rooted in play, corporeal sensibility and emancipation, has the potential to enact social change and enhance entrepreneurial potential.